Intelligent Control and Innovative Computing - Ao, Sio Iong.; Ao, Sio Iong.; Castillo, Oscar.; Castillo, Oscar.; Huang, He.; Huang, He. (Lecture Notes in Electrical Engineering, 2012)
In the lightning-fast world of intelligent control and cutting-edge computing, it is vitally important to stay abreast of developments that seem to follow each other without pause. This publication features the very latest and some of the very best current research in the field, with 32 revised and extended research articles written by prominent researchers in the field. Culled from contributions to the key 2011 conference Advances in Intelligent Control and Innovative Computing, held in Hong Kong, the articles deal with a wealth of relevant topics, from the most recent work in artificial intelligence and decision-supporting systems, to automated planning, modelling and simulation, signal processing, and industrial applications. Not only does this work communicate the current state of the art in intelligent control and innovative computing, it is also an illuminating guide to up-to-date topics for researchers and graduate students in the field. The quality of the contents is absolutely assured by the high profile of the 250 members of the IMECS (International Multi-Conference of Engineers and Computer Scientists) committees who come from more than 30 countries and who supervised the selection of papers.